Developing English E-Vocabulary Module as Supplementary Book of Computer Learning Program - Iin Widya Lestari; Moch. Iswahyudi Putra (PT ARRUS Intelektual Indonesia, 2023)
This research aims to develop an electronic English module that can be used by computer/ IT learners do deeply learn computer programming. It employes Research and Development (RnD) method by applying 4D steps namely define, design, develop and disseminate. Questionnaire is used as instrument and curriculum analysis is done to get the whole description and topic analysis. The result reveals that 83% of alumna agreed that computer learner needed the module that contain the definition of word that used in computer. While the curriculum analysis reveals that some main topics consists of 3 main subjects namely Microsoft word, Microsoft Excel, and Microsoft PowerPoint. There are two experts gave judgement and validation regarding to the product. The first expert is from English Language practitioner that validate and judges the content and language aspects. The result reveals that module got 4,7 with maximal score is 5. The second expert is from computer/ IT practitioner. He concerns on validating material, appearance, and media and technical terms on the module. The result shows that 4.4 with the maximal score is 5. It can be implied that both experts judge module is appropriate to be used as supplementary material for computer course.